ANALISIS PEMETAAN FUNGSI WAKTU PRODUKSI PADA HOME INDUSTRI (COSH MOTOR) JASA PEMBUATAN ONDERDIL MOTOR DI PASURUAN - Siti Rochmaniyah (Universitas muhammadiyah malang, 2017)
The research objective was to overcome the problem of wastage of time in the production processed by planning the mapping function of time for workers andowners of home industry for the production processed to avoid waste of time andreduce the damage.The analytical tool used was a function mapping the basis forknowing which processes were causing wastage of time. The analysis shows the mapping function of time base production processed itcan be seen, there were four processed were experiencing wastage of time that wascontrolling the processed, waiting for turning, waiting for staining, and warehouse,with two factors, namely the engine and human issues. Of the two factors, theproblem may be known solution was to increase the machine and provide training toemployees to avoid errors in the production processed. In addition to the mappingfunction target time in order to indicate whether the implemented solution hadprovided an increase in the production processed and the company's operations canbe run effectively and efficiently.